Successful Treatment of Recurrent Dermatitis after Physalia physalis (Portuguese Man O' War) Envenomation with Extracorporeal Shock Wave Therapy - Leandro Dellanna; Frank Hirche; Vasile Capra (Karger Publishers, 2021)
For more than 3 decades, extracorporeal shock wave therapy (ESWT) has been clinically implemented in urologic and orthopaedic indications. Here, we present the case of a patient with envenomation from a highly toxic jellyfish-like siphonophore (Physalia physalis) with a toxic contact dermatitis resulting in chronic eruptive skin lesions. The skin lesions on the dorsal right hand lasted more than 16 weeks and were refractive to local cortisone treatment. They finally healed after 8 applications of low-energy planar/defocused ESWT over 4 weeks. In detail, the clinical course, ESWT specifications and the possible mechanisms of ESWT in the light of the current literature are discussed. Our case indicates that ESWT is an underestimated, promising non-invasive, non-immunosuppressive treatment for chronic eruptive skin lesions after jellyfish or related toxin envenomations.